2021
DOI: 10.3390/en14185720
|View full text |Cite
|
Sign up to set email alerts
|

The Future Is Colorful—An Analysis of the CO2 Bow Wave and Why Green Hydrogen Cannot Do It Alone

Abstract: In both the private and public sectors, green hydrogen is treated as a promising alternative to fossil energy commodities. However, building up production capacities involves significant carbon production, especially when considering secondary infrastructure, e.g., renewable power sources. The amount of required capacity as well as the carbon production involved is calculated in this article. Using Germany as an example we show that the switch to purely green hydrogen involves significant bow waves in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Hence, the dataset is sufficient to estimate the effects of various strategies, as tested in Section 4. For wind power, we use the numbers and assumptions from [2], and for solar power, the numbers from [8]. Let us assume 900 full load hours (flh) for solar power at a lifetime of 20 years.…”
Section: Data Sources and Core Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the dataset is sufficient to estimate the effects of various strategies, as tested in Section 4. For wind power, we use the numbers and assumptions from [2], and for solar power, the numbers from [8]. Let us assume 900 full load hours (flh) for solar power at a lifetime of 20 years.…”
Section: Data Sources and Core Assumptionsmentioning
confidence: 99%
“…One major pillar is the German hydrogen (H 2 ) strategy 2030 [1] that aims to reduce carbon emissions, mainly in the fields of industry and transport. Von [2] showed that this strategy would imply a significant carbon bow wave, as well as bow waves in financial and resource demand terms. Based on an economic model, the authors derived the necessity to include turquoise hydrogen, i.e., hydrogen based on natural gas, as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the two preceding processes, SMR and POX, are combined, the result is known as autothermal reforming (ATR). In this way, POX, in conjunction with O 2 , provides the energy required for SMR, thereby rendering the process thermally neutral [51]. It requires less energy than other processes due to its high thermal efficiency.…”
Section: Hydrogen Production From Fossil Fuelsmentioning
confidence: 99%
“…By the adaptation of different technology and considered sources, hydrogen production has been categorized into three types according to the literature and study reports (von Döllen et al, 2021;Noussan et al, 2021). The utilization of major sources for the production of hydrogen has introduced the color conceptualization.…”
Section: Categorization Of Hydrogen Based On the Source Of Generationmentioning
confidence: 99%